(untitled) (Edinburgh, 2008)
This is book introduction about principles of clinical pharmacology, clinical pharmacokinetics, Adverse drug reactions, The pharmacology of the autonomic nervous system...
Dược lý
Keywords: Veterinary drugs,Veterinary pharmacology,Veterinary Drugs,Drug therapy,Thuốc thú y,Thuốc thú y,Liều lượng thuốc; Pharmacokinetics,Veterinary,Tác dụng của tới cơ thể,Thú y